2022
DOI: 10.1027/0227-5910/a000782
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Changes of Suicide Probability During COVID-19 Among Chinese Weibo Users

Abstract: Abstract. Background: Coronavirus disease 2019 (COVID-19) threatens people's physical and mental health, globally, and it may even trigger suicide ideation and suicidal behavior. Aims: We aimed to examine the impact of COVID-19 on suicide risk by sampling Chinese Weibo users and analyzing their social media messages. Method: We predicted the probability of suicide (including hopelessness, suicidal ideation, negative self-evaluation, and hostility) of Weibo users in order to assess the changes in suicide probab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…During the pandemic, people have been experiencing psychiatric disorders, such as fear ( 35 , 36 ), stress, anxiety ( 37 ), disappointment, irritability, depressive disorders, and even suicide ( 38 ). The COVID-19 pandemic also has a dynamic impact on suicide probability ( 39 ). This study indicated that we could take steps to reduce the spread of suicide reports during COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…During the pandemic, people have been experiencing psychiatric disorders, such as fear ( 35 , 36 ), stress, anxiety ( 37 ), disappointment, irritability, depressive disorders, and even suicide ( 38 ). The COVID-19 pandemic also has a dynamic impact on suicide probability ( 39 ). This study indicated that we could take steps to reduce the spread of suicide reports during COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…In previous research the measurement of emotions was mostly based on existing API [43,48], psychological scale [16], or only from the perspective of words and themes [5] rather than scenario-based analysis. However, emotions are comprehensive manifestations of not only words but also contexts.…”
Section: Emotional Disclosure On Social Media In Quarantinementioning
confidence: 99%
“…In light of the virus transmission mechanism and the unprecedented sphere of influence, quarantine, a direct and effective social distancing strategy, is adopted by most governments around the world [73]. However, an emerging body of research warns of the exacerbated threat of vigorous confinement for the public's mental health under quarantine, like depression [12], suicide [48], and post-traumatic stress disorder (PTSD) [36]. Understanding mental health challenges during quarantine is warranted for further research to propose supporting technologies and improve intervention measures that could help the public obtain psychological balance.…”
Section: Introductionmentioning
confidence: 99%
“…Since the outbreak of COVID-19, people's negative emotions have increased, and their life satisfaction has decreased [17]. COVID-19 also has a dynamic effect on suicide probability [18]. There are many research methods for determining the public's psychological state on Weibo, such as machine learning [19], qualitative content analysis [20], and so on.…”
Section: Introductionmentioning
confidence: 99%